THE LEVEL OF FAMILY WELFARE FISHERMEN IN SUNGAI NIPAH, IN IV JURAI, PESISIR SELATAN VILLAGE, THE PROVINCE OF WEST SUMATERA - Sari, Nori Novita; Yulinda, Eni; ', Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was condud at Sungai Nipah village, IV Jurai ditrict, Pesisir Selatan Regency, West Sumatera Province on july 2015. This research aimed to know characteristics and walfare fishermen society at Sungai Nipah village, IV Jurai, District Pesisir Selatan regency, West Sumatera Pronce, The mothed use was survey mothed, The respondets were 38 fisherman depend on sensus methed The result from this research, showed that walfare average by BPS with eight indicator, such as income, consumption, home condition, home facility, familyhealth, health facility, education family, transfortation family. Walfare fisherman sociely in the Sungai Nipah villageis moderate category with amounting 37 fisherman (97,37%) and the other walfare fisherman so society is low category amounting fisherman (2,63%) so walfare fishermen society at Sungai Nipahvillage in the” high categoty” is nothing. Keyword: welfare, fisherman, Family